2020
DOI: 10.5194/hess-24-1649-2020
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and shade trees show complementary use of soil water in a traditional agroforestry ecosystem

Abstract: Abstract. Globally, coffee has become one of the most sensitive commercial crops, being affected by climate change. Arabica coffee (Coffea arabica) grows in traditionally shaded agroforestry systems in tropical regions and accounts for ∼70 % of coffee production worldwide. Nevertheless, the interaction between plant and soil water sources in these coffee plantations remains poorly understood. To investigate the functional response of dominant shade tree species and coffee (C. arabica var. typica) plants to dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 68 publications
(105 reference statements)
3
25
0
Order By: Relevance
“…For more than 25 million small coffee farmers, challenges such as climate change [32] have a drastic impact on coffee production. Plants and grains are very sensitive to global warming, especially the Coffea Arabica [33] which represents around 60-70% of world coffee production [34], [35]. It is estimated that 54% of coffee crops are expected to reach temperatures above 32°C by 2050 [36].…”
Section: A Coffee Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more than 25 million small coffee farmers, challenges such as climate change [32] have a drastic impact on coffee production. Plants and grains are very sensitive to global warming, especially the Coffea Arabica [33] which represents around 60-70% of world coffee production [34], [35]. It is estimated that 54% of coffee crops are expected to reach temperatures above 32°C by 2050 [36].…”
Section: A Coffee Productionmentioning
confidence: 99%
“…Produced in more than 70 countries, the largest amount of coffee is produced in developing countries, and the largest consumption of beverage is in developed countries, whose growing demand has doubled the amount of coffee grown in the last decade [45], [46]. Coffee production also has challenges related to shading, carbon sequestration, pest control, soil properties [34], [47] and rust and plant disease that can reduce productivity by up to 50% [48]. It is also important to mention that coffee agriculture and commercialization are responsible for a large volume of harmful waste that generates major environmental impacts.…”
Section: A Coffee Productionmentioning
confidence: 99%
“…Hence, the null model attributes any variance in isotopic composition to extraction errors with maximum extraction error ranges of 3 ‰ for δ 2 H samples (0.3 ‰ for δ 18 O) expected for water extraction recovery rates higher than 98 % (e.g., Orlowski et al, 2013). These extraction errors are negatively skewed following the Rayleigh distillation model which predicts that extraction error for incomplete water recovery will be negative and therefore Obs.…”
Section: The Null Modelmentioning
confidence: 99%
“…et al, 2016) are collected and analyzed for their stable isotope composition. The stable isotope composition of the different collected water has allowed researchers to develop new theories whether plants use soil-bound vs. mobile soil water pools (Brooks et al, 2010) or consume water from specific soil layers that change over time (Berry et al, 2018;Beyer et al, 2016;Goldsmith et al, 2012;Koeniger et al, 2016;Muñoz-Villers et al, 2020). Amin et al (2020) compared results from different stable isotopes studies performed in natural catchments and deduced that plants in dry tropical climates consume water from soil layers deeper than 50 cm.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that stable isotopes have been used to a lesser extent in agricultural systems than in natural systems to investigate plant water sources (Penna et al, 2020), there are successful studies done in coffee (Muñoz-Villers et al, 2020), maize, wheat (Stumpp et al, 2009) and rice cultures (Mahindawansha et al, 2018;Shen et al, 2015). In the case of rice, Shen et al (2015) observed that flooded rice consumed soil water from 0-15 cm deep, while Mahindawansha et al (2018) found that upland rice in dry conditions mostly consumed soil water from up to 50 cm deep except during the maturing stage, when plants shifted to use water from the 10-30 cm soil depth.…”
Section: Introductionmentioning
confidence: 99%